A Semiempirical Quantum Approach to the Formation of Carbon Dioxide Adsorbates on Pt(100) and Pt(111) Cluster Surfaces - Zinola Sánchez, Carlos Fernando (1998)
The geometries and binding energies of CO2 adsorbates on Pt(100) and Pt(111) cluster surfaces were calculated by means of an improved version of the extended Hückel molecular orbital method. The polarization of the surface by an applied electric potential and coadsorption of H atoms were included in the model. For simulated applied potentials in the range -1.0 to 1.0 V, CO2 coordination geometries (side-on, formate) involving two adsorbate atoms bonded to the surface are favored, regardless the surface topology and the presence of coadsorbed H atoms. In agreement with experiment, larger binding energies are always calculated for the Pt(100) cluster surface.